PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI RESTORAN SAJIAN SAMBARA GREEN TERRACE - Tidar Bayu Sakti; Hariadi Hadisuwarno (LPPM Universitas Asa Indonesia, 2019)
This study aims to determine the influence of product , price and promotion on purchacing decision simultaneously and partially to purchase decision. The sample used in this study are the consumer at Sajian Sambara Restaurant, totally 100 respondents. The sampling technique by purposive, due to time and cost efficiency. The instrument has been tested its validity and reliability prior to the survey. Data analyzed by multiple linear regression wuith the classic assumption test (normality, multicollinearity, heteroskedasticity, and linearity test) while hypothesis testing includes F test, T test, and partial analysis test and coefficient of determination (R2). The results showed that product quality, price, and promotion has a significant influence on consumer loyalty either partially and simultaneously.